Combined 30-degree bevel up and down technique against 0-degree phaco tip for phacoemulsification surgery of hard cataracts - Joshi RS (Dove Medical Press, 2017)
Rajesh Subhash Joshi, Sonal Jayant Muley Department of Ophthalmology, Vasantrao Naik Government Medical College, Yavatmal, Maharashtra, India Purpose: To evaluate the effective phaco time (EPT), cumulative dissipated energy (CDE) and nucleus emulsification time (NET) as phaco parameters with 0- and 30-degree phaco tip. Patients and methods: This prospective, interventional and observational case series included 294 patients scheduled for cataract removal by phacoemulsification technique. Patients with nuclear cataracts of grade 4 and 5 nuclear opalescence of Lens Opacities Classification System III were included in the study. Patients were consecutively allocated to phaco chop technique with 0-degree (0-degree group, n=147) and combined bevel up and down position using 30-degree phaco tip (combined bevel up/down group, n=147). The 0-degree group had phacoemulsification with 0-degree phaco tip, while the 30-degree group had chopping of the nucleus with bevel down phaco tip and emulsification of nuclear fragments was accomplished with bevel up tip. EPT, CDE, NET and intraoperative complications were noted and compared between the groups using analysis of variance. Results: Average EPT, CDE and NET were lower in the 30-degree group than in the 0-degree group. However, no statistically significant difference was found in EPT (P=0.0733), CDE (P=0.0663) and NET (P=0.0633) between the two groups. No serious intraoperative complications were noted. The anterior chamber was maintained throughout the procedure in both groups. No patients had wound burn and miosis during the procedure. None of the patients developed bullous keratopathy, uveitis and cystoid macular edema during the follow-up period. Conclusion: Combined bevel up and down 30-degree tip can yield effective hard nucleus phacoemulsification. Bevel down tip of 30-degree helps in effective chopping and bevel up tip assists in emulsification of the nuclear fragments. Although combined bevel up and down 30-degree tip can yield effective hard nucleus phacoemulsification, no statistically significant difference was found in EPT, CDE and NET between the two groups. Keywords: phacoemulsification, bevel up and bevel down phaco needle, effective phaco time, cumulative dissipated energy